Development and validation of a software application to analyze thermal and kinematic multimodels of Stirling engines - Auñón-Hidalgo, Juan Antonio; Pérez, José M.; Martín-Sánchez, María Jesús; Auñón, Fernando; Nuñez, Daniel (Elsevier, 2023)
The work developed presents, for the first time, a tool to analyze all the thermodynamic models used in the study and development of Stirling engines: isothermal, ideal adiabatic and adiabatic with losses, combined adiabatic thermodynamic with finite speed (CAFS), thermodynamic with finite speed (FST), ideal polytropic and polytropic with losses (PSVL), allowing a comparative study of them. This software (ASCE-UMA), designed and implemented in a Matlab GUI® allows to obtain the operating parameters of these engines, calculating the thermodynamic parameters, power output and efficiency. Additionally, the thermodynamic models can be evaluated with different me- chanical configurations, for which different drive mechanisms are implemented: Sinusoidal, Alfa Ross yoke types, Alfa Ross V yoke, Beta rhombic type and free piston Stirling engine (FPSE). Thermoacoustic and other, models could be analyzed by virtue of their similarity of movement with some of the implemented models. In the same way, ASCE-UMA allows the study of various exchanger configurations, as well as various regenerator models. The versatility of ASCE-UMA allows the development analysis of all the fundamental elements of a new prototype as well as the analysis of experimental data by performing a customized and detailed calculation. To test the effectiveness of ASCE-UMA, its performance is verified by analyzing Ross Yoke D-90 models and a GM GPU-3 engine. This is a tool that allows to analyze and comparing the different models and the different existing mechanisms for the multiple configurations of Stirling engines in an easy and intuitive application with a high-quality graphical interface.
Keywords: Motores térmicos; Ingeniería mecánica; Thermodynamic modelling; CFD simulation; Stirling calculation; Stirling mechanisms